Career Adaptability of Prospective Teachers with Disabilities in Indonesia: A Phenomenological Study - Badriyah, Rr Dwi Umi; Ramadhani, Erfan; Putri, Ramtia Darma; Sari, Syska Purnama; Sarmento, Amândio de Araújo; Mat, Seda Tuğba Baykara; Suhardita, Kadek (Jurnal Kajian Bimbingan dan Konseling, 2026)
Pre-service teachers with disabilities face career transitions shaped by personal aspirations, accessibility barriers, stigma, and limited role models. In Indonesia, little is known about how they build career readiness for teaching within inclusive unequal educational contexts. This study explores the career adaptability of pre-service teachers with disabilities in Indonesia. Grounded in Career Construction Theory, it examines concern, control, curiosity, and confidence, while extending the framework by considering resilience and flexibility as relevant dimensions. A qualitative phenomenological design was used. Twenty-five students with disabilities enrolled in Primary School Teacher Education and Special Education programs at an Indonesian university participated in semi-structured interviews. Data were analyzed using interpretative phenomenological analysis to capture participants' lived experiences in preparing for careers in education. The findings show that career adaptability developed through six interconnected dimensions. Concern emerged through career awareness, teac‘hing practice, and disability role models. Control was reflected in career planning, barrier management, and priority adjustment. Curiosity involved exploring alternative pathways, using varied information sources, and engaging in cross-disciplinary collaboration. Confidence was strengthened by successful teaching experiences and support, but weakened by discrimination. Resilience enabled participants to recover from rejection, while flexibility supported adaptation to teaching methods, technologies, and professional roles. Inclusive mentoring, experiential learning, accessibility support, and disability-sensitive career guidance are essential to strengthen work readiness and advance an inclusive educational workforce.